2016
DOI: 10.1093/pcp/pcw150
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of Specific Threonine and Tyrosine Residues in Arabidopsis CERK1 is Essential for the Activation of Chitin-Induced Immune Signaling

Abstract: Pattern recognition receptors on the plant cell surface mediate the recognition of microbe/damage-associated molecular patterns (MAMPs/DAMPs) and activate downstream immune signaling. Autophosphorylation of signaling receptor-like kinases is a critical event for the activation of downstream responses but the function of each phosphorylation site in the regulation of immune signaling is not well understood. In this study, 41 Ser/Thr/Tyr and 15 Ser/Thr residues were identified as in vitro and in vivo autophospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…A most recent study showed that flg22 and elf18 induce BAK1 phosphorylation at Ser602, Thr603, Ser604 and Ser612 in vivo, and these four phosphosites are required for flg22 but not brassinosteroid (BR) signalling [20]. In addition to serine/threonine phosphorylation, an increasing number of RLKs have been shown to undergo tyrosine phosphorylation, and this modification is important for their activation [20][21][22][23]. A Tyr residue is present in kinase subdomain VIa (Tyr-VIa) and conserved in about 80% Arabidopsis LRR-RLKs.…”
Section: Regulation Of Protein Phosphorylation and Stability In Pattementioning
confidence: 99%
“…A most recent study showed that flg22 and elf18 induce BAK1 phosphorylation at Ser602, Thr603, Ser604 and Ser612 in vivo, and these four phosphosites are required for flg22 but not brassinosteroid (BR) signalling [20]. In addition to serine/threonine phosphorylation, an increasing number of RLKs have been shown to undergo tyrosine phosphorylation, and this modification is important for their activation [20][21][22][23]. A Tyr residue is present in kinase subdomain VIa (Tyr-VIa) and conserved in about 80% Arabidopsis LRR-RLKs.…”
Section: Regulation Of Protein Phosphorylation and Stability In Pattementioning
confidence: 99%
“…Arabidopsis seedlings were collected 2 h after the 100 lg ml À1 LPS (P. aeruginosa) or 20 lM (GlcNAc) 7 treatments. Gene expression was quantified by reverse transcription real-time PCR using Fast SYBR Green Master Mix (Thermo Fisher Scientific Inc., Waltham, MA, USA) (Suzuki et al, 2016). Actin was used as the internal control.…”
Section: Ros Production and Gene Expression Assaysmentioning
confidence: 99%
“…This band shift was previously confirmed to show the autophosphorylation of CERK1. 9 On the other hand, the band of CERK1(Y428F)-3HA did not show such an upward shift, indicating that the mutant CERK1 was not phosphorylated in N. benthamiana. These observations are different from the results of previous in vitro kinase assay where the heterologously expressed kinase domain of this mutant was normally autophosphorylated and indicated that Y428 plays a pivotal role in the in vivo activation of CERK1 kinase required for downstream defense signaling.…”
mentioning
confidence: 93%
“…[5][6][7] It has been shown that the kinase activity of CERK1 is essential for the activation of immune responses and CERK1 itself is phosphorylated by chitin treatment. 8,9 Petutschnig et al identified four or five in vivo phosphorylation sites of CERK1 and showed that the phosphorylation of at least three of them was dependent on chitin treatment. 8 Recently, we also identified 41 in vitro and 15 in vivo phosphorylation sites of CERK1 and indicated that at least three of them play important roles in chitin signaling based on the complementation experiments with the CERK1 mutants of these phosphorylation sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation